ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENJUALAN PADA RESTORAN MAKANAN JEPANG (STUDI KASUS PT. SUSHI INDO SUKSES MANDIRI) - Dakhi, Santa Ana; Junaidi, Listya Devi; Syaharman, Syaharman (Worksheet : Jurnal Akuntansi, 2023)
The purpose of this study is to ascertain how PT. Indo Success Mandiri's sales are impacted by product,pricing, and marketing. Quantitative research is the kind that was employed. ways for gathering datawhile using a questionnaire. 150 PT. Indo Independent Success personnel made up the study's sample.The study's sample consists of 60 workers. data source that included primary and secondary data.Multiples were processed with SPSS version 2016 using linear regression analysis. The study's findingsare evident. With a value of 40.52%, these variables have an impact concurrently, and the remaining59.48% is partially influenced by other variables that were not included in this study. The relationshipbetween the product and sales at the Japanese food restaurant PT. Indo Mandiri success is significantat 35%, the relationship between the price and sales at the Japanese food restaurant PT. Indo SuksesMandiri is significant by 60.7%, and the relationship between the promotion and sales at the Japanesefood restaurants PT. Indo Sukses Mandiri is significant at 30.0%.